2014
DOI: 10.3390/molecules19044145
|View full text |Cite
|
Sign up to set email alerts
|

Optical Absorption of the Antitrypanocidal Drug Benznidazole inWater

Abstract: UV-vis optical absorption spectra of the antitrypanocidal drug benznidazole solvated in water were measured for various concentrations. The spectra show a prominent peak around 3.80 eV, while deconvolution of the UV-vis optical absorption spectra revealed six bands centered at 3. 60, 3.83, 4.15, 4.99, 5.60, and 5.76 eV. Benznidazole electronic transitions were obtained after density functional theory (DFT) calculations within the polarized continuum (PCM) model for water solvation. Molecular geometry optimiza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 19 publications
(28 reference statements)
1
7
0
1
Order By: Relevance
“…3) showed that the BZN@CaCO 3 had an absorbance peak at 324 nm, the same observed for BZN (Bezerra et al . 2014). Through the linear interpolation of the BZN absorbance (at 324 nm) in different dilutions (calibration curve), the BZN concentration was determined in the conjugated form as being ~25%.…”
Section: Resultsmentioning
confidence: 99%
“…3) showed that the BZN@CaCO 3 had an absorbance peak at 324 nm, the same observed for BZN (Bezerra et al . 2014). Through the linear interpolation of the BZN absorbance (at 324 nm) in different dilutions (calibration curve), the BZN concentration was determined in the conjugated form as being ~25%.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, one can also determine partial atomic charges and dipole moments both of which are essential to mimic charge transfer (CT) states. 58,59 As previously mentioned, the method compliments UV-Vis spectroscopy, where the relative intensities of the optical transitions can also be determined.…”
Section: Computational Methods: Density Functional Theory (Dft)mentioning
confidence: 99%
“…Theoretical quantum chemistry methods based on HF and DFT are used for the calculation of optimized geometry, absorption spectrum, FT-IR and 1 H NMR spectra of the organic molecules. [5][6][7][8][9][10][11][12][13][14][15][16][17] In this work on the basis of PVA and new synthesized dichroic azo benzene dye A thermostable polarizing film absorbing in visible spectral range of spectrum (λ max = 550 nm) for application in Display Technologies and Optoelectronic applications was developed.…”
Section: Introduction *mentioning
confidence: 99%